2015
DOI: 10.1038/jcbfm.2015.97
|View full text |Cite
|
Sign up to set email alerts
|

CX3CL1/CX3CR1-Mediated Microglia Activation Plays a Detrimental Role in Ischemic Mice Brain via p38MAPK/PKC Pathway

Abstract: The exact roles of activated microglia and fractalkine (CX3CL1)/fractalkine receptor (CX3CR1) signaling are not fully understood in brain ischemic injury and the findings reported are controversial. Here, we investigated the effects of CX3CR1 siRNA on the expression of CX3CR1, p38 mitogen-activated protein kinase (p38MAPK), Protein Kinase C (PKC) and inflammatory cytokines, microglia activation, white matter lesions, and cognitive function in mice treated with bilateral common carotid artery stenosis (BCAS) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(56 citation statements)
references
References 47 publications
1
55
0
Order By: Relevance
“…Consistent with these reports, administration of the selective microglial inhibitor, minocycline, attenuated microglial activation, decreased IL-1β production, protected developing oligodendrocytes, and attenuated white matter injury in neonatal rat brains [194, 195]. Similarly, inhibition of CX3CR1, a receptor involved in microglial chemotaxis, decreased microglial activation, reduced IL-1β production, attenuated white matter injury, and improved neurocognitive function in a pre-clinical model of vascular cognitive impairment [196]. While the aforementioned findings suggest a detrimental role for microglia after TBI, minocycline failed to attenuate traumatic axonal injury, tissue atrophy, neurodegeneration, or spatial learning deficits in a pediatric head trauma model [197].…”
Section: Is Microglial Activation the Cellular Link Between Damp Rmentioning
confidence: 57%
“…Consistent with these reports, administration of the selective microglial inhibitor, minocycline, attenuated microglial activation, decreased IL-1β production, protected developing oligodendrocytes, and attenuated white matter injury in neonatal rat brains [194, 195]. Similarly, inhibition of CX3CR1, a receptor involved in microglial chemotaxis, decreased microglial activation, reduced IL-1β production, attenuated white matter injury, and improved neurocognitive function in a pre-clinical model of vascular cognitive impairment [196]. While the aforementioned findings suggest a detrimental role for microglia after TBI, minocycline failed to attenuate traumatic axonal injury, tissue atrophy, neurodegeneration, or spatial learning deficits in a pediatric head trauma model [197].…”
Section: Is Microglial Activation the Cellular Link Between Damp Rmentioning
confidence: 57%
“…Dex overcame the effect of Glu on phagocytosis (Figure D–F). Glu enhanced the expression of mRNA encoding the microglial markers Iba1, CD11b, and CX3CR1 (Liu et al, ) (Figure Ga–Gc). Glu also increased mRNA encoding F4/80 (Lin et al, ), CD68 (Sugimoto et al, ), matrix metalloproteinase 2 (MMP2) (Lively and Schlichter, ), cathepsin S (Hayashi et al, ; Lively and Schlichter, ), and interferon regulatory factor 1 (IRF1) (Higaki et al, ) (Figure Gd–Gh), which have been suggested to participate in phagocytosis, migration, modulation of synapses, or activation of microglia, respectively.…”
Section: Resultsmentioning
confidence: 90%
“…CXCR1 and ERK/p38 MAPK inhibition decreased activation of microglia and blockade of this route also attenuated lesions to the white matter, and the cognitive impairments induced by BCAS (Lee et al, 2013; Liu et al, 2015). …”
Section: Discussionmentioning
confidence: 99%